Inbreeding evaluation using microsatellite confirmed inbreeding depression in growth in the Fenneropenaeus chinensis natural population - Lyu, Ding; Sun, Song; Shan, Xiujuan; Wang, Weiji (Frontiers in Genetics, 2023)
Understanding inbreeding depressions (IBD), the effects on phenotypic performance of inbreeding, are of major importance for evolution and conservation genetics. IBD in aquatic animals were well documented in domestic or captive population, while relatively there is less evidence of IBD in natural populations. Chinese shrimp, Fenneropenaeus chinensis, is an important species in both aquaculture and fishery activities in China. To investigate IBD in natural populations, four F. chinensis natural populations (Huanghua, Qinhuangdao, Qingdao and Haiyang) were collected from the Bohai and Yellow Seas. Microsatellite markers were used to evaluate individual inbreeding coefficients (F) of all samples. Furthermore, effects of inbreeding on growth trait were investigated. The results showed marker based F were continuous and ranged from 0 to 0.585, with an average of 0.191±0.127, and there was no significant difference among the average F of four populations. Regression analysis using four populations showed inbreeding had a very significant (p<0.01) effect on body weight. When analyzing single population, regression coefficients were also all negative and those in Huanghua and in Qingdao were significant at the level of p<0.05 and <0.01, respectively. IBD, expressed as the percent change in body weight per 10% increase in F, were 2.75% in Huanghua, 2.22% in Qingdao and 3.69% in all samples. This study provided a piece of rare evidence of IBD in natural populations and also guidance to conservation of wild F. chinensis resources.